Peruntōṭṭak kaittoḻilil peṇ toḻilāḷarkaḷiṉ paṅku = The role of the female worker in the plantation industry (Seminar report (Sri Lanka Foundation Institute), 1978)
Report of the seminar organized by the Sri Lanka Foundation Institute, 1977.